Contornos da cultura : representações sobre o processual e o dinâmico no registro de bens culturais de natureza imaterial como patrimônio cultural do Brasil - Zacchi, Marina Sallovitz (2017)
This research is directed to the practice of the anthropologist in the frames of the State, to the stress processed in the appropriation and instrumentalization of the theoretical basis of anthropology for the elaboration and implementation of a brazilian public policy focused on protection and promotion of the cultural heritage of immaterial nature, which has been said to be guided by the principle of culture by anthropology. Initially, I seek to carry out an archaeology of the notion of culture, proposing that this should be understood according to the successive layers of discourses and practices with what was being outlined and that inform the uses that are made even in present times, reflecting on the ways because the binding between cultural heritage and identity places the difference locus in the public policy that display the diversity. Then – with support in understanding where I see the most significant points of friction between the theoretical basis of anthropology and the intangible heritage policy protection guided by the anthropological concept of culture, system, interaction and reflexivity – I see while discursive practices the dossiers that register as Brazil's cultural heritage some cultural assets, chosen as emblematic of the uses of these notions in the execution of this specific public policy, seeking to point out how these different uses induce social intervention actions guided by different principles and purposes or different ideological positions.